Integrasi Nilai-Nilai Kearifan Lokal Masyarakat Duakoran dalam Pembelajaran Sosiologi di SMAN Raimanuk East Nusa Tenggara - Hubertus Klaran (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this study was to find out how the integration of the local wisdom values of the Duakoran community in sociology learning at Raimanuk High School. The research method used was qualitative. The research subjects using the purposive sampling techniques consisted of the principal of SMAN Raimanuk, sociology subject teachers, and students of SMAN Raimanuk. Research data were collected through in-depth interviews, observations, field notes, and document analysis. The research data were analyzed using qualitative analysis techniques moving in a circle between data collection, data reduction, data presentation, and data verification. This research shows that integrating local wisdom values into learning activities means integrating, incorporating, and applying values that are believed to be good and correct in order to form, develop, and foster the character or personality of students according to national identity when learning activities take place. One of the values of local wisdom that is integrated into teaching materials is the learning process in the activities of the hase hawaka (greetings and greetings) tradition.